The system of professional training for foreign language teachers in Bukovina (1918-1940): the history of the fragmented land - Labinska B., Morska L., Homeniuk O. (Paedagogica Historica. International Journal of the History of Education. Routladge Taylor&Francis Group, 2022)
The article describes the key features of the system of foreign language teacher professional training in Bukovina in 1918 to 1940. Bukovina is an area of present-day Western Ukraine, which in the period under study belonged to Romania. The study has been carried out in the form of an analysis of the components constituting the system of foreign language teacher education: the discussion begins with the preconditions for establishing pedagogical practices in training future teachers from the historical-social and administrative-territorial perspectives; then the structural aspects and educational policymaking issues of the institutions responsible for foreign language teacher training in Bukovina, as well as their activities aimed at providing professional support for in-service teachers, have been studied; finally, the structure and content of both the curricula and textbooks used in foreign language teachers’ education have been critically analysed. The deliberations brought the authors to conclude that the methods of teaching foreign languages most widely used and supported by the government in the period under study in Bukovina were the Direct and Mixed methods. At the same time, the analysis of governmental policy of the ruling state contributed to the process of Romanianisation of the Ukrainians, depriving young people of the opportunity to gain secondary and higher education in their native language, while discriminating against the school graduates on their ethnicity as the criterion for enrolment of university applicants for a degree in teaching foreign languages.
Keywords: Bukovina, foreign language, teacher, teacher training, foreign language learning